The phytoremediation potential for strontium of indigenous plants growing in a mining area - Şaşmaz, Ahmet; Şaşmaz, Merve (My University, 2009)
This study investigated the distribution and accumulation of strontium (Sr) in the shoots and roots of Euphorbia macroclada (EU), Verbascum cheiranthifolium (VR), and Astragalus gummifer (AS), with respect to their potential use in phytoremediation. Plant samples and their associated soils were collected from the arid and semi-arid Keban mining area andwere analyzed inductively by ICP-MS for Sr. Mean Sr values in the shoots, roots and soil were, respectively, 453, 243 and 398mg kg?1 for E. macroclada; 149, 106 and 398mg kg?1 for V. cheiranthifolium; and 278, 223 and 469mgkg?1 for A. gummifer. The enrichment factors for root (ECR) and shoot (ECS) of these plants were lower than 1 or close to 1, except for the shoot of E. macroclada. The mean translocation factors (TLF) of these plants were higher than 1 and 2.08 for E. macroclada, 1.47 for V. cheiranthifolium, 1.18 for A. gummifer. It thus appeared that the shoots of these plants can be an efficient bioaccumulator plant for Sr and it can be used in cleaning or rehabilitating of the contaminated soil and areas by Sr because of their high translocation factors.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Enrichment coefficient; Phytoremediation; Strontium; Translocation factor; Plant soil; Uptake